Photocatalytic degradation kinetics of naphthenic acids in oil sands process-affected water: Multifactorial determination of significant factors. (December 2016) - Leshuk, Tim; de Oliveira Livera, Diogo; Peru, Kerry M.; Headley, John V.; Vijayaraghavan, Sucharita; Wong, Timothy; Gu, Frank
Abstract: Oil sands process-affected water (OSPW) is generated as a byproduct of bitumen extraction in Canada's oil sands. Due to the water's toxicity, associated with dissolved acid extractable organics (AEO), especially naphthenic acids (NAs), along with base-neutral organics, OSPW may require treatment to enable safe discharge to the environment. Heterogeneous photocatalysis is a promising advanced oxidation process (AOP) for OSPW remediation, however, predicting treatment efficacy can be challenging due to the unique water chemistry of OSPW from different tailings ponds. The objective of this work was to study various factors affecting the kinetics of photocatalytic AEO degradation in OSPW. The rate of photocatalytic treatment varied significantly in two different OSPW sources, which could not be accounted for by differences in AEO composition, as studied by high resolution mass spectrometry (HRMS). The effects of inorganic water constituents were investigated using factorial and response surface experiments, which revealed that hydroxyl (HO) radical scavenging by iron (Fe 3+ ) and bicarbonate (HCO3 − ) inhibited the NA degradation rate. The effects of NA concentration and temperature on the treatment kinetics were also evaluated in terms of Langmuir-Hinshelwood and Arrhenius models; pH and temperature were identified as weak factors, while dissolved oxygen (DO) was critical to the photo-oxidation reaction. Accounting for all of these variables, a general empirical kinetic expression is proposed, enabling prediction of photocatalytic treatment performance in diverse sources of OSPW. Graphical abstract: Highlights: Rate of photocatalysis varied significantly in OSPW from different tailings ponds. HO scavenging by Fe 3+ and HCO3 − inhibited the NA degradation rate. Temperature and pH minimally affected treatment rate, while DO was essential. An empirical kinetic expression is given for photocatalysis in OSPW.